Políticas públicas para a efetividade do direito à educação superior no Brasil: direitos humanos e sociais através da educação superior - Carmona, Raquel Torcani (2021)
Education has the power to transform the lives of young people, promoting the increase of their social and economic perspectives. It is proposed to appoint public policies to encourage the entry of a large number of young people aged between 17 to 24 in higher education, since this measure promotes greater economic growth for Brazil and better income distribution, with a reduction in social inequalities. Through bibliographical and documentary analysis several authors and studies demonstrate the importance of higher education for people's lives, such as high employability, a significant increase in wages and job maintenance in times of crisis for those who complete higher education. It evidenced that a low percentage of the young registered in institutions of superior education in the country, therefore the vacant in the free public institutions are insufficient. Private institutions are responsible for the great part of the available seats, charging monthly fees that are not accessible for the great majority of the population. This study observed that government programs, as the Program University for All (ProUni) and Higher Education Student Financing Fund (Fies), had been essential for the ingression and permanence of the students in higher education. It concluded that programs of the state that promote access to higher education are effective and essential for the inclusion of the young in higher education and considers alternatives of public politics for this matter